Analisis Manajemen Risiko Aplikasi SINTESA Pada Perpustakaan XYZ - Pangestu, Rifky Prima; Wijaya, Agustinus Fritz (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2021)
The Sintesa application is an operation support information system application that functions to assist the XYZ Library in recording loan books, a list of available books, the number of books, book loan maturities, and a list of book borrowers. In implementing this information system, there are certain risks that will hinder the process or function of the system, so a risk analysis is needed to prevent the risks that will occur. By using ISO 31000 in the XYZ library, it is hoped that it can minimize the possible risks that will occur around the SINTESA application. The results of the risk analysis with ISO 31000 in the form of documentation of possible risks that exist around the SINTESA application, classifying the possibilities - risks based on their impact. So that the results of this risk analysis can be used by the library to prevent and minimize risks and treat these risks according to the impact or risk priority that may occur in the library application